Analisis Wacana Kritis Berita Penerapan Revolusi Mental - Feri Sanjaya (Oratio Directa (Prodi Ilmu Komunikasi), 2018)
Abstract"The Mental Revolution." The term that President Soekarno first used in 1957 when the national revolution was stopped. The mental revolution is a movement aimed at galvanizing the Indonesian man into a new man of white heart, steel-bearing, eagle-eagled spirit, sparkling fire. One part of the Mental Revolution is law enforcement. Law enforcement is a process of real efforts to enforce legal norms as a guide to traffic behavior or legal relations in the life of society and state. The press as part of the pillar of democracy has a role in the effort of realizing law enforcement through its preaching. The role of mass media can not be underestimated. In certain cases, indirectly media can assist in defending the small people from oppression. Mass media can also make giving direction to government policy in order to always pro people, do not emphasize merit of elite. In social media coverage, quotes from the President's statement about the Mental Revolution from each individual are widely disseminated, but have never been interesting to talk about by readers because they are still dominated by negative things. In fact, the implementation of the Mental Revolution has been initiated in various government bureaucratic environments, especially as conducted by the Indonesian Police, the Attorney General's Office, the Corruption Eradication Commission (KPK) and the Ministry of State Apparatus Empowerment and Bureaucratic Reform (PAN RB). The existing news dynamics tend to be more dominantly distributed, such as: "Papa Asks for Stocks", "Komjen Budi Waseso", "Multiple Positions", and "Setya Novanto Case". Key Word: Mental Revolution, Press, Law EnforcementAbstrak “Revolusi Mental.” Istilah yang pertama kali digunakan Presiden Soekarno tahun 1957 ketika revolusi nasional sedang berhenti. Revolusi mental adalah sebuah gerakan yang ditujukan untuk menggembleng manusia Indonesia agar menjadi manusia baru yang berhati putih, berkemauan baja, bersemangat elang rajawali, berjiwa api yang menyala-nyala. Salah satu bagian dari Revolusi Mental adalah penegakan hukum. Penegakan hukum merupakan suatu proses dilakukannya upaya tegaknya norma-norma hukum secara nyata sebagai pedoman perilaku lalu lintas atau hubungan-hubungan hukum dalam kehidupan bermasyarakat dan bernegara. Pers sebagai bagian dari pilar demokrasi mempunyai peran dalam usaha mewujudkan penegakan hukum melalui pemberitaannya. Peran media massa tak bisa disepelekan. Pada kasus-kasus tertentu, secara tak langsung media dapat membantu dalam membela rakyat kecil dari penindasan. Media massa juga dapat membuat memberi arah kebijakan pemerintah agar selalu pro rakyat, tidak mementingkan segolongan elit semata. Dalam pemberitaan media sosial, kutipan pernyataan Presiden mengenai Revolusi Mental mulai dari setiap individu cukup banyak disebarkan, namun belum pernah menjadi yang menarik untuk dibicarakan oleh pembaca karena masih didominasi hal-hal yang negatif. Padahal, pelaksanaan Revolusi Mental telah digagas di berbagai lingkungan birokrasi pemerintahan, khususnya seperti yang dilakukan oleh Kepolisian RI, Kejaksaan Agung, Komisi Pemberantasan Korupsi (KPK) dan Kementerian Pemdayaan Aparatur Negara dan Reformasi Birokrasi (PAN RB). Dinamika pemberitaan yang ada cenderung negatif malah lebih dominan disebarkan misalnya tentang: “Papa Minta Saham”, “Komjen Budi Waseso”, “Rangkap Jabatan”, dan “Kasus Setya Novanto.Kata kunci : Revolusi Mental, Pers, Penegakan Hukum